2018
DOI: 10.3748/wjg.v24.i35.4021
|View full text |Cite
|
Sign up to set email alerts
|

Biosimilars in paediatric inflammatory bowel disease

Abstract: The introduction of biological treatments has changed disease outcomes for patients with inflammatory bowel disease. Biologicals have high efficacy, and can induce and maintain remission after failed responses to conventional immunosuppressive and/or steroid therapy. The increasing occurrence of severe disease at diagnosis has resulted in infliximab being more often introduced as the first-line treatment in a “top-down” approach. Besides their favourable efficacy and safety profile, biologicals have one signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…On the other side, a few healthcare organizations (HCOs) believed that biosimilars were complex proteins and could never be identical similar of the therapeutics agents. 2,[7][8][9] Despite such conflicts, biosimilars are used in numerous European countries and are getting approved in the United States and the rest of the world. 1,2 Cost-effectiveness, prescription patterns, dispensing practices and patients' belief about efficacy and safety of biosimilars are among the vital factors which are expressively essential to understand.…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, a few healthcare organizations (HCOs) believed that biosimilars were complex proteins and could never be identical similar of the therapeutics agents. 2,[7][8][9] Despite such conflicts, biosimilars are used in numerous European countries and are getting approved in the United States and the rest of the world. 1,2 Cost-effectiveness, prescription patterns, dispensing practices and patients' belief about efficacy and safety of biosimilars are among the vital factors which are expressively essential to understand.…”
Section: Introductionmentioning
confidence: 99%
“…The first biosimilar used in Europe contained somatropin [recombinant human growth hormone (rhGH)] [ 5 ]. These new medicines have now become a big part of biological therapies used by many specialists in the treatment of rheumatoid arthritis, cancer, Crohn’s diseases, colitis, diabetes mellitus, osteoporosis, anaemia, immunologic diseases and other ailments, both in adults and in children [ 6 – 8 ]. At the time of writing (2018), 15 originator biological drugs had corresponding centrally authorised biosimilar medicines, which have been approved for therapy by the EMA (47 products), including adalimumab, bevacizumab, enoxaparin sodium, epoetin alfa, epoetin zeta, etanercept, filgrastim, follitropin alfa, infliximab, insulin glargine, insulin lispro, pegfilgrastim, rituximab, somatropin, teriparatide and trastuzumab [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…After conducting a number of in-depth analyses, the authors concluded that switching to biosimilar infliximab was the perfect solution to reduce treatment costs by 10-30% without compromising patient treatment. 18 Sarosiek T. and Morawski P. draw attention to the improved patient access to adequate therapy after the introduction of biosimilar medicinal products, in particular trastuzumab, and also identify reductions in treatment costs due to increasing competition. 19 Kim J. et al estimate the cost savings between 2011 and 2014 as a result of the use of biosimilar infliximab on the South Korean market.…”
Section: Discussionmentioning
confidence: 99%